Estrategias de marketing de Procolombia en el turismo de cruceros en Cartagena de Indias: análisis de implementación en los años 2009 hasta 2014 (2016)
In this investigation there are analyzed the strategies of marketing implemented by Procolombia to attract the tourism of cruises to the city of Cartagena de Indias, dividing from the year 2009 until 2014. The study was realized across consultations to indexed databases and governmental web sites. There was obtained like proved the identification of some policies proposed by the Department of Trade, Industry and Tourism of Colombia to attract international tourists and It marks country, which is the strategy of marketing used by Procolombia to stimulate the exports, to promote investments and to attract foreign tourists. The behavior that has had the tourism of cruises in the city has been favorable, is characterized by his constant growth.